P228 Ultrasound for assessing disease activity in ulcerative colitis: Development of a novel ultrasonographic disease activity index. (16th January 2018) - Bots, S; Nylund, K; Löwenberg, M; Gecse, K; Gilja, O H; D'Haens, G
Abstract: Background: Trans-abdominal ultrasound (US) is useful for detection of inflammation in ulcerative colitis (UC) patients. Up to now, no validated disease severity index exists. We aimed to develop an ultrasonographic activity index using endoscopy as reference standard. Methods: UC patients undergoing endoscopy in standard care were eligible for inclusion. US was performed within 3 weeks from endoscopy without treatment change. Endoscopists and ultrasonographers were blinded for the other examination. The recorded US parameters included bowel wall thickness (BWT), Doppler signal (DS), colonic haustrations, wall layer stratification (WLS), fatty wrapping and presence of reactive lymph nodes. DS was categorised as absent, small spots or large spots/stretches. Disease activity was categorised according to the endoscopic Mayo score. US and endoscopic findings were compared for each colon segment except for the rectum. Normally distributed parameters were compared with unpaired T-tests. Categorical parameters were compared with logistic regression. ROC curves were made to determine optimal cut-off values for BWT. The most predictive parameters and cut-off values were used to construct a point based UC-US index. The index was calculated for each patient and compared with the overall Mayo score using the Spearman's rank correlation test. Results: Sixty patients were included and 208 colon segments were endoscopically explored. Mean BWT was significantly different between all Mayo categories, except for Mayo 2 vs. 3. BWT > 2.1 mm was best to discriminate between Mayo 0 and Mayo 1–3 (Sens 83.5%; Spec 91.5% ), a cut-off of 3.2 mm was best to discriminate between Mayo 0-1 and Mayo 2–3 (Sens 93.5%; Spec 91.8%) and BWT >3.9mm was best for detection of Mayo 3 (Sens 86.2;%; Spec 82.7%). DS was predictive for active (i.e. ≥Mayo 1) disease (OR 25.1; 95% CI 10.5–60.2). Large spots/stretches of DS were associated with Mayo 2–3 (OR 48.6; 95% CI 11.0–214.8). Loss of haustrations was associated with active disease but did not discriminate between Mayo categories (OR 144.0; 95% CI 41.1–504.1). The presence of fatty wrapping was associated with severe disease (OR 39.6; 95% CI 6.7–233.3). The UC-US score was calculated for each patient by adding points for BWT (1–3), DS (1–2), loss of haustrations (1) and presence of fatty wrapping (1). The global UC-US score showed high correlation with overall endoscopic disease activity (Þ = 0.844; p < 0.001). Conclusions: An ultrasonographic UC disease activity index was developed that showed excellent correlation with endoscopic disease activity. This index needs to be validated in future prospective studies and tested for sensitivity to change.